GMOs: need for appropriate risk assessment system - Bhargava, Pushpa M. (2002)
There is an urgeng need for setting up a Biotechnology Commission which would in turn determine the monitoring and policy making machanisms in the field. For, such bodies not only need to have technical expertise, but have to work within a well-developed social perspective. - Reproduced.
Keywords: Biotechnology